2012
DOI: 10.1128/jvi.02301-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Mammalian Species-Infectious and -Pathogenic H6N5 Avian Influenza Virus without Evidence of Adaptation

Abstract: c An H6N5 avian influenza virus (AIV) strain, designated A/aquatic bird/Korea/CN5/2009 (H6N5), was isolated from fecal swabs of aquatic birds in 2009, and surprisingly, it showed infectivity and pathogenicity in mammalian species without evidence of adaptation. In this study, we report the first complete genome sequence containing 3= and 5= noncoding regions (NCRs) of a mammalian species-infectious and pathogenic H6N5 AIV, which will help provide important insights into the molecular basis of pathogenesis, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…While the lengths of the 3′ and 5′ NCRs of the viral RNA of A/feline/Korea/01/2010 (H3N2) were variable (19 to 45 and 20 to 58 nt at the 3′ and 5′ NCRs, respectively) in the different genome segments, the terminal 12 and 13 nt of the 3′ and 5′ ends, respectively, were highly conserved (3′-UCGYUUUCGUCC- and -GGAACAAAGAUGA-5′) among all eight genome segments, which is consistent with previous studies (13, 14, 19, 20). Surprisingly, 1 nt was changed between the start codon (UAC) and the conserved region (UCGYUUUCGUCC) in the 3′ NCR of Seg-1 and also in Seg-6 of A/feline/Korea/01/2010 (H3N2) compared to A/canine/Korea/01/2007 (H3N2).…”
Section: Genome Announcementsupporting
confidence: 90%
“…While the lengths of the 3′ and 5′ NCRs of the viral RNA of A/feline/Korea/01/2010 (H3N2) were variable (19 to 45 and 20 to 58 nt at the 3′ and 5′ NCRs, respectively) in the different genome segments, the terminal 12 and 13 nt of the 3′ and 5′ ends, respectively, were highly conserved (3′-UCGYUUUCGUCC- and -GGAACAAAGAUGA-5′) among all eight genome segments, which is consistent with previous studies (13, 14, 19, 20). Surprisingly, 1 nt was changed between the start codon (UAC) and the conserved region (UCGYUUUCGUCC) in the 3′ NCR of Seg-1 and also in Seg-6 of A/feline/Korea/01/2010 (H3N2) compared to A/canine/Korea/01/2007 (H3N2).…”
Section: Genome Announcementsupporting
confidence: 90%
“…1A and B). To validate these HA and NA ssNCR sequence logos, we also examined the NCR sequences from the literature, which were determined accurately by specific NCRsequencing methods (27,(32)(33)(34)(35)(36), and compared them with the sequence logos generated from the bioinformatics analysis (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that, within each segment-specific NCR, most nucleotides are highly conserved, whereas, at certain nucleotide positions, the identities of nucleotides are variable (most of them are transition changes). We further validated these sequence logos by comparing them with the NCR sequence logos determined by accurate NCR sequencing methods (Park et al, 2013(Park et al, , 2012Su et al, 2012;Wang & Lee, 2009;. We found that the majority of nucleotide conservation/variation at each nucleotide position was generally consistent between the sequence logos (Fig.…”
Section: Bioinformatics Analysis Of the Segment-specific Non-coding Rmentioning
confidence: 83%